Chest Wall Prostheses for Pectus Excavatum and Poland Syndrome Using 3D-Printed Models: Technique and Outcomes After 25 Years' Experience - P Dargan, Dallan; L Touil, Leila; Woolley, Gina; Shaaban, Hassan (International Journal of Surgical Techniques, 2019)
Background: Chest wall deformities may be managed with skeletal manipulation, which risks life-threatening complications. Custom-made prostheses are a less invasive surgical option, manufactured from silicone elastomer using 3D computed tomographic reconstruction and 3D-printed thoracic models. Methods: All patients undergoing custom-made implants between January 2010 and March 2017 were identified from the prosthetic department records. A retrospective review of the clinical records was performed. Mean follow up period was 1.8 years. A comparison was made with our earlier results from 1995 to 2009. Results: Twenty-six patients underwent insertion of custom-made implants for chest wall deformity. Pectus excavatum was present in 50% (n=13), and Poland syndrome 42% (n=11). All 11 female patients underwent 3D reconstruction and 3D printed models, and 3 of 15 males. Four underwent simultaneous bilateral breast augmentation, and three had staged breast augmentation. Seroma occurred in 27% (n=7), and hypertrophic scar in 12% (n=3). The reoperation rate was 23% (n=6), including autologous fat graft in two patients. Surgical suction drains were used in 42% (n=11) patients, of whom 36% (n=4) developed seroma, compared with 17% (n=2) of those without drains (p=0.08). Conclusions: Custom-made prostheses are an effective and safe option for patients with chest wall deformities. The majority have a short postoperative inpatient stay (81%) and are satisfied with the outcome (77%). Seroma was the commonest complication (27%), and drains did not reduce seroma risk. Single dose intravenous antibiotic prophylaxis is adequate. A minority of patients opt for further aesthetic procedures.
Keywords: prosthesis; Poland syndrome; pectus excavatum; silicone elastomers; seroma; 3D printing.